2022
DOI: 10.1177/21514593221099375
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Is Associated With a 4 Fold Increase in 30-day Mortality Risk in Hip Fracture Patients in the United Kingdom: A Systematic Review and Meta-analysis

Abstract: Background Hip fracture in elderly patients is associated with a significant mortality which may be worsened by COVID-19 infection. Objective To undertake a systematic review and meta-analysis of studies assessing the effect of COVID-19 infection and mortality rates in hip fracture patients in the United Kingdom (UK) during the first surge of the pandemic. Design A systematic literature search of 9 online databases was undertaken independently by 2 reviewers using the Cochrane methodology for systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Another systematic review and meta-analysis discovered that patients with hip fractures who had concomitant COVID-19 infection had a 34% short-term mortality rate [ 13 ]. Mastan et al found that COVID-19 status was associated with a 4-fold increase in mortality among patients with hip fractures [ 14 ]. In a study conducted by Raheman, patients with hip fractures who had COVID-19 had a 4-fold risk of mortality (risk ratio: 4.59, p < 0.0001), and the 30-day mortality rate was 38% (hazard ratio: 4.73, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review and meta-analysis discovered that patients with hip fractures who had concomitant COVID-19 infection had a 34% short-term mortality rate [ 13 ]. Mastan et al found that COVID-19 status was associated with a 4-fold increase in mortality among patients with hip fractures [ 14 ]. In a study conducted by Raheman, patients with hip fractures who had COVID-19 had a 4-fold risk of mortality (risk ratio: 4.59, p < 0.0001), and the 30-day mortality rate was 38% (hazard ratio: 4.73, p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review to determine the mortality of concomitant infection of COVID-19 with hip fractures, Mastan et al showed the 30-day mortality was 32.5% in COVID-positive patients compared to 8.3% in COVID-negative patients [ 20 ]. But the mortality rates among vaccinated patients are not available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have suggested that the vaccine is less effective in elderly frail patients [ 17 ]. Hip fractures are commonly seen in elderly frail patients and are associated with high mortality when infected with concomitant COVID-19 [ 18 - 20 ]. The effectiveness of the vaccine in hip fractures may be crucial in reducing the mortality among these patients but there is no evidence depicting the same at present.…”
Section: Discussionmentioning
confidence: 99%
“…Expectedly, there was also a surge in hip fracture patients with concomitant COVID-19 infection. Although meta-analyses have illustrated a significantly higher mortality rate in COVID-19 patients with a hip fracture [ [4] , [5] , [6] ], most studies were of Caucasians. High quality cohort data regarding mortality and complications is still lacking amongst Asian populations [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%